Potential prebiotic substrates modulate composition, metabolism, virulence and inflammatory potential of an in vitro multi-species oral biofilm - Verspecht, Tim (J Oral Microbiol, 2021)
Background: Modulation of the commensal oral microbiota constitutes a promising preventive/therapeutic approach in oral healthcare. The use of prebiotics for maintaining/restoring the health-associated homeostasis of the oral microbiota has become an important research topic. Aims: This study hypothesised that in vitro 14-species oral biofilms can be modulated by (in)direct stimulation of beneficial/commensal bacteria with new potential prebiotic substrates tested at 1 M and 1%((w/v)), resulting in more host-compatible biofilms with fewer pathogens, decreased virulence and less inflammatory potential. Methods: Established biofilms were repeatedly rinsed with N-acetyl-D-glucosamine, α-D-lactose, D-(+)-trehalose or D-(+)-raffinose at 1 M or 1%((w/v)). Biofilm composition, metabolic profile, virulence and inflammatory potential were eventually determined. Results: Repeated rinsing caused a shift towards a more health-associated microbiological composition, an altered metabolic profile, often downregulated virulence gene expression and decreased the inflammatory potential on oral keratinocytes. At 1 M, the substrates had pronounced effects on all biofilm aspects, whereas at 1%((w/v)) they had a pronounced effect on virulence gene expression and a limited effect on inflammatory potential. Conclusion: Overall, this study identified four new potential prebiotic substrates that exhibit different modulatory effects at two different concentrations that cause in vitro multi-species oral biofilms to become more host-compatible.